Belajar Matematika Lebih Mandiri: Peran Metode PSI dalam Pemahaman Konsep Matematika Siswa - Hardiana Hardiana; Sartika Arifin; Fauziah Hakim (FKIP Universitas Mataram, 2026)
The purpose of this study was to determine the effect of the personalized system of instruction (PSI) Method on the understanding of mathematical concepts of class XI MPLB students of SMKN 1 Tinambung. This type of research is a quantitative study with quasy eksperimental design methode with a nonequivalent control group design, the sampling technique is purposive sampling. This research was conducted at SMKN 1 Tinambung in the 2025/2026 academic year with class XI MPLB 1 as the control class and XI MPLB 2 as the experimental class. Research data were collected using a mathematical concept understanding ability test and observation sheets. Research data analysis consisted of descriptive analysis and inferential analysis. The results of the descriptive analysis show that the average test score for students' mathematical concept understanding ability in the experimental class is in the good category, while the average test score for students' mathematical concept understanding ability in the control class is in the sufficient category. The results of the inferential analysis using the t test (independent sample t test) showed that there was an effect of the personalized system of instruction (PSI) method on the understanding of mathematical concepts of class XI MPLB students of SMKN 1 Tinambung.